Capacidad funcional en adultos mayores usuarios de una unidad médica ubicada en la zona marginal en Guerrero, México. - Chávez-Rojas, Ana Karina; García-Morales, Gabriela; Garduño-Orbe, Brenda; Gil-Ojeda, Ricardo (Revista Horizonte Médico)
Objective: To identify factors associated with functional capacity in older adults attending a medical unit located in a marginalized area of Guerrero, Mexico. Materials and methods: This was a cross-sectional, analytical study involving 379 individuals aged 60 years or older, of both sexes. Data were collected from January to June 2024 using non-probability convenience sampling. Older adult beneficiaries of the family medicine unit who agreed to participate in the study were included, while those with difficulties in autonomy or verbal communication were excluded. Functional capacity in basic activities of daily living was assessed using the Barthel index, and perceived satisfaction with basic family functions was evaluated using the APGAR questionnaire. Categorical variables are presented as frequencies and proportions, while quantitative variables are expressed as measures of central tendency and dispersion. Pearson's chi-square test was applied to identify factors associated with functional dependence. Results: A total of 379 beneficiaries were included in the study. The age range was 60 to 95 years, with a predominance of females. Overall, 90.23 % presented with chronic diseases, with high blood pressure being the most common. Moreover, 49.34 % were independent, while 8.44 %, 35.35 % and 6.59 % presented with mild, moderate, and severe disability, respectively. Regarding family support, 68.86 % perceived it as good. Non-modifiable variables associated with dependence were age, educational level, and presence of chronic diseases, while modifiable variables were polypharmacy, sedentary lifestyle, and not engaging in recreational activities. Conclusions: Healthcare personnel should promote physical activity and recreational strategies among older adults attending the healthcare unit, as well as reduce the number of prescribed medications to prevent the prescribing cascade. Such measures may help prevent functional dependence among older adults.